Perancangan Sistem Informasi Perpustakaan SMP Berbasis Web Menggunakan QR-Code - Nugroho, Ismail Adji; Umar, Rusydi (Journal of Information System Research (JOSH), 2024)
The development of information technology is currently very fast and has become a necessity in all fields, one of which is information systems in school libraries. Many libraries in various schools, both public and private, still use conventional or manual methods to manage data in their libraries. Aisyiyah Bantul Unggulan Middle School is an Islamic education-based school that has a library that still uses conventional methods, namely the process of borrowing books still using a borrowing card and then entering it into Excel, so it takes quite a long time, besides making it difficult for library administration in managing books and searching for books. With the construction of this system, it is hoped that it can assist in the process of borrowing books, assist the library administration in managing book data and loading reports, and make it easier for students to obtain information. The method for developing this library information system uses the Waterfall method. So it makes it easier to complete the website development process because there are stages in this method starting from communication, planning, modeling, construction, to delivery, while for the system testing process using the black box testing method, the results obtained are that the system runs without there is a problem and the features work fine. With this system, it is hoped that it will provide significant benefits in assisting the book borrowing process by using QR-Code scans, assisting library administration in managing existing book data and assisting in creating reports and making it easier for students to obtain information on existing books.